Kajian Implementasi Smart Environment di Kota Bandung - Farhan Fauzan; Ernady Syaodih (Jurnal Riset Perencanaan Wilayah dan Kota, 2022)
Abstract. Smart environment is one of the axes of the smart city concept that has been implemented in the Bandung city. The implementation of smart environment is focused on urban environmental problems that occur in the Bandung city, especially in Sukajadi District. In Sukajadi District itself, environmental problems still occur, ranging from flooding, issues of waste management, drainage, rivers, to the availability of green open spaces. Therefore, in this study the author will try to identify the extent to which the implementation of the smart environment in Sukajadi District is based on 14 indicators, namely (1) green building; (2) sustainable-certified buildings; (3) smart homes; (4) renewable energy; (5) pollution control and management with ICT; (6) household and industrial waste control; (7) management of water resources and improvement of clean water quality standards; (8) river revitalization; (9) waste management; (10) street lighting; (11) drainage system; (12) provision of green open space; (13) slum area management; and (14) urban farming. The purpose of this research is to identify the extent of the implementation of the smart environment, identify problems related to the smart environment, and identify what strategies and development programs can be applied in implementing the smart environment in Sukajadi District. This study uses qualitative and quantitative methods using SWOT analysis. Data were collected through observations and interviews with every relevant stakeholder such as Regional Apparatus Organizations (OPD), District Government, Kelurahan and Sukajadi Subdistrict communities. The results of the analysis are strategies that can be implemented in a smart environment in Sukajadi District. Abstrak. Smart environment merupakan salah satu sumbu dari konsep smart city yang sudah diterapkan di Kota Bandung. Implementasi smart environment ini berfokus pada permasalahan lingkungan perkotaan yang terjadi di Kota Bandung khususnya di Kecamatan Sukajadi. Di Kecamatan Sukajadi sendiri permasalahan lingkungan kerap masih terjadi, mulai dari banjir, isu pengelolaan sampah, drainase, sungai, hingga terkait ketersediaan ruang terbuka hijau. Oleh sebab itu dalam penelitian ini penulis akan mencoba untuk mengidentifikasi sudah sejauh mana implementasi dari smart environment di Kecamatan Sukajadi ini yang didasarkan pada 14 indikator yaitu (1) green building; (2) sustainable-certified buildings; (3) smart homes; (4) energi terbarukan; (5) pengendalian dan pengelolaan polusi dengan TIK; (6) pengendalian limbah rumah tangga dan industri; (7) pengelolaan sumber daya air dan peningkatan baku mutu air bersih; (8) revitalisasi sungai; (9) pengelolaan sampah; (10) penerangan jalan; (11) sistem drainase; (12) penyediaan RTH; (13) pengelolaan kawasan kumuh; dan (14) urban farming. Tujuan dari penelitian ini adalah untuk mengidentifikasi sejauh mana implementasi dari smart environment, mengidentifikasi permasalahan terkait smart environment, dan mengidentifikasi strategi program pengembangan apa saja yang dapat diterapkan dalam implementasi smart environment di Kecamatan Sukajadi. Penelitian ini menggunakan metode kualitatif dan kuantitatif dengan menggunakan analisis SWOT. Data data dikumpulkan melalui observasi dan wawancara dengan setiap stakeholder terkait seperti Organisasi Perangkat Daerah (OPD), Pemerintah Kecamatan, Kelurahan serta masyarakat Kecamatan Sukajadi. Hasil analisisnya berupa strategi yang dapat diimplementasikan dalam smart environment di Kecamatan Sukajadi.